The Effect of Swimming with Reduced Breathing Frequency on Blood Lactate Concentration - Tsalis, Γεώργιος; Poularinos, Γεώργιος; Loupos, Δημήτριος; Mougios, Βασίλης (Inquiries in Physical Education and Sport, 2009)
Training with reduced breathing frequency (hypoxic training) is used by swimming coaches to strengthen the respiratory muscles and increase the capacity to exercise under anaerobic, or apnoic, conditions. However, opinions differ regarding the effects of hypoxic training on the swimmers’ physiology. The purpose of the present research was to compare the blood lactate concentration and heart rate after submaximal swimming with different breathing frequencies. Seven male and seven female adolescent swimmers performed two freestyle 8 × 50 m trials at 91 ± 2 % of their most recent record. During one trial, the swimmers breathed normally, while during the other they breathed every 7-8 armstrokes. Capillary blood samples were obtained before and 3, 5 and 7 min after the end of each trial to determine the lactate concentration. Furthermore, heart rate was recorded before and immediately after each trial. Data analysis showed no significant differences between the normal compared to the reduced breathing frequency trials on lactate (13.8 ± 4.2 vs. 13.6 ± 3.1 mmol/L) or heart rate (180 ± 8 vs 176 ± 13 bpm). In conclusion, blood lactate and heart rate were not affected by the breathing pattern during submaximal swimming training.